Chiral ammonium betaine-catalyzed asymmetric Mannich-type reaction of oxindoles - Torii, Masahiro; Kato, Kohsuke; Uraguchi, Daisuke; Ooi, Takashi (Beilstein Journal of Organic Chemistry, 2016)
A highly diastereo- and enantioselective Mannich-type reaction of 3-aryloxindoles with N-Boc aldimines was achieved under the catalysis of axially chiral ammonium betaines. This catalytic method provides a new tool for the construction of consecutive quaternary and tertiary stereogenic carbon centers on biologically intriguing molecular frameworks with high fidelity.
Keywords: ammonium betaine; asymmetric catalysis; Mannich reaction; organocatalysis; oxindole